The Degree of Landscape Openness as a Manifestation of Cultural Metamorphose - Plit, Joanna; Myga-Piątek, Urszula (Quaestiones Geographicae, 2014)
The issues of aesthetic assessment of landscapes has now become important due to the need of rational and balanced cultural landscape management and the implementation of the provisions of the European Landscape Convention. The aim of this article is to show the methodology of the assessment and interpretation of the degree of the current openness of the cultural landscape of Poland as an effect of a historical process. The chronological analysis made it possible to single out stages of opening/enclosing of the landscapes of Poland with reference to crucial natural, historical and cultural factors. The degree of landscape openness may be treated as a synthetic indicator of the natural and cultural environment evolution. When a landscape type is viewed as a result of natural and anthropogenic processes, the analysis of proportions between the surface of natural and cultural elements becomes of prime importance. In the historical times, the process of landscape enclosing was not unidirectional. Four stages of transformation of cultural landscapes in Poland have been distinguished. These stages are characterized by differences of the landscape openness. It can be interpreted as the result of cultural metamorphosis.